Cherubinis celebrate (Raton Range Raton, New Mexico, 1984)
Newspaper Article on the 50th Anniversary of Mr. & Mrs. Frank Cherubini.
Master list item #: 20
File location is in the Raton File Cabinet
Keywords: Cherubini, Frank; Cherubini, (Mrs.); Cherubini, Celeste; Slease, Verlene; Milkovich, Angelina; Milkovich, Edward; Milkovich, Kathryn; Milkovich, Mike; Moran, Peggy; Andreoli, Bernard; Andreoli, (Mrs.); Wear, Janet; Andreoli, (Mrs.) John; Bergamo, Ann; Kelly, Martin; Bergamo, Angelo; Bergamo, (Mrs.); Overdorf, Richard; Overdorf, (Mrs.); Martinez, Ken; Martinez, (Mrs.); Slease, William; James, David; James, (Mrs.); Andreoli, Linda; Andreoli, Lynette; Haner, Charles; Haner, (Mrs.); Andreoli, Eliott; Andreoli, (Mrs.); Andreoli, Ginelle; Andreoli, Sam; Heringa, Mary; Harkness, Virginia; Pasquale, Carl; Pasquale, (Mrs.); Edwards, James; Edwards, (Mrs.); Jaterka, Carlo; Jaterka, (Mrs.); Harkness, Tim; Harkness, Dan; Raton Country Club; Local History; Biography; Life and Customs; Marriage; Celebration; Anniversary; Raton, New Mexico; Albuquerque, New Mexico; Sepulveda, California; Denver, Colorado; Aurora, Colorado; Colorado Springs, Colorado; Las Cruces, New Mexico; Eagle Nest, New Mexico; Springer, New Mexico